2006
DOI: 10.1038/sj.bjc.6603468
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of S-1 monotherapy in metastatic colorectal cancer after failure of irinotecan- and oxaliplatin-containing regimens

Abstract: This is the first phase II study of S-1 monotherapy for patients with metastatic colorectal cancer after failure of both irinotecan-and oxaliplatin-containing regimens. The initial dose of S-1 was 35 mg m À2 , administered twice daily for 14 days every 3 weeks. Treatment was repeated until the occurrence of disease progression. Twenty-eight patients were enrolled. S-1 was administered to 21 patients as third-line therapy and to the remaining seven patients as fourth-line therapy. Of 26 evaluable patients, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…We assumed that the S-1-induced anemia was related to erythropoiesis rather than bleeding or hemolysis, based on the following: (a) the anemia occurred continuously after initial treatment; (b) there existed interpersonal variability in the velocity of mean Hb reduction per cycle after S-1 treatment; (c) 6 weeks per cycle is long enough to affect erythropoiesis by S-1; (d) there was gradual macrocytosis with S-1 treatment (from 91 to 106 fl of mean corpuscular volume), reflecting deranged DNA synthesis and mitosis; and (e) the anemia comprised a unique toxicity profile of the S-1-treated Korean population in colorectal cancer [40]. Based on these findings, we tried to find genetic changes that are related to S-1-induced anemia with pharmacogenomic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…We assumed that the S-1-induced anemia was related to erythropoiesis rather than bleeding or hemolysis, based on the following: (a) the anemia occurred continuously after initial treatment; (b) there existed interpersonal variability in the velocity of mean Hb reduction per cycle after S-1 treatment; (c) 6 weeks per cycle is long enough to affect erythropoiesis by S-1; (d) there was gradual macrocytosis with S-1 treatment (from 91 to 106 fl of mean corpuscular volume), reflecting deranged DNA synthesis and mitosis; and (e) the anemia comprised a unique toxicity profile of the S-1-treated Korean population in colorectal cancer [40]. Based on these findings, we tried to find genetic changes that are related to S-1-induced anemia with pharmacogenomic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…(1) S-1-related adverse reactions commonly appear 2 -3 weeks after treatment starts (Nagashima et al, 2005); (2) a 2-week schedule showed the possibility of mitigated toxicity and prolonged the medication period (Kimura et al, 2003); (3) this schedule showed feasibility in heavily pretreated metastatic colorectal cancer (Jeung et al, 2006); and (4) recent phase I study of 2-week S-1 schedule demonstrated an antitumour activity in chemotherapy-refractory gastric cancer, with a similar pharmacokinetic profile to the conventional schedule (Zhu et al, 2007).…”
Section: S-1 Monotherapy In Poor Performance Status H-c Jeung Et Almentioning
confidence: 99%
“…Anemia is a unique side effect found in Korean gastric and colorectal cancer patients after S-1 monotherapy (8,9,15). Factors contributing to the ethnic differences in toxicity are clinical status of the patient, pharmacokinetics, pharmaco- dynamics, pharamacogenetics especially in genes with drug metabolism, and pharmacogenomics.…”
Section: Discussionmentioning
confidence: 99%